AKTIVITAS, KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PROJECT BASED LEARNING PICTURE AND PICTURE DAN TALKING STICK DI SDN PEMURUS DALAM 6 BANJARMASIN - Rezqia Maulida; Amberansyah (STKIP Subang, 2025)
Students in six second-grade classes at SDN Pemurus have problems with critical thinking skills, lack of activity, and poor learning outcomes. If they are not engaged and do not understand the concepts correctly, learning becomes boring and useless. Classroom action research is the qualitative methodology employed in this study. In order to ascertain whether a project-based learning model, photographs and photos, and Talking Sticks could enhance critical thinking abilities, learning outcomes, student activity, and instructor activity, this study was carried out over the course of four sessions during the 2024–2025 academic year. Success indicators for the data collected included individual completion rates of 70% and classical completion rates of 82%. Teachers scored 31 in the